Entre palavras e imagens: O legado artístico de rossini perez. - Rodrigues, Marisa Pires (2016)
This work analyzes Rossini Perez constitution process of personal archive in order to record his personal, artistic and cultural history, comprising memory as a guiding principle. For this, documentary qualitative research free conversations were thematic oral history associated as a collection technique. Within this context, we studied the obtained material structure in his ethos information. The result demonstrates an autobiographical writings from the personal collection, considered as a rich heritage of experiences, which recognize Rossini Perez as one of major international fame Brazilian engraver.